Age of first breeding and incidence of dystocia and losses at parturition and post-partum in indigenous Nigerian pig - Osuagwuh, A.I.A.; Akpokodje, J.U. (1981)
Studies were carried out on the prevalence of dystocia and losses at parturition and post-partum following early mating and first breeding in 15 Nigerian indigenous pigs six were 8 months old at the time of there first farrowing, while nine were 11 or 12 months at the time of their first farrowing. Forty-six piglets were born, of which 11 or 12 months at the time of there first farrowing. Forty-six piglets were born, of which 11 died at birth (24%) and a further 18 during the next 7 days (total loss 63.0%). The six pigs that farrowed at 8 months of age had smaller mean litters and births weights, a higher incidence of dystocia and higher piglet mortality at birth than those that farrowed later (32 with 91 % survival). However, increased age at first farrowing did not reduce the high death rate during the first week (50% of Piglets which survived at birth in both groups). This was attributed to starvation due to poor mothering ability following first farrowing since there was no agalactia or mastitis.